“Collaborativе Еcosystеms and Knowlеdgе Crеation: Analysis of Dеtеrminants and Mеchanisms - Al-Omoush, Khaled Saleh; Gomez-Olmedo, Ana M. (Transformations In Business & Economics, 2024)
The main aim of this study is to explore the potential role of Social Capital (SC) and Collaborative Culture (CC) in participation in Collaborative Ecosystems (CES) and the impact of these ecosystems on creating Collaborative Knowledge Innovation (CKI). This study also aims to examine the potential impact of organisational learning, resource sharing and digital transformation as mechanisms that mediate the impact of participation in CES on CKI. To conduct this empirical study, data was collected from 257 managers of technology companies. Smart PLS was used to estimate the research model and test hypotheses. The results show that SC and CC in participation in CES significantly impact participation in CES. The findings also reveal that organisational learning, resource sharing and digital transformation play significant mediating roles in the relationship between CES and CKI. The findings of this study provide valuable theoretical and practical insights into the link between these determinants and mechanisms integrated into a unified framework.